Natural Gas in Peru and the Projects Destined to its Decentralization - Abanto Bojórquez, Jesús Alejandro (2014)
Last August marked 10 years since the start of the Camisea project, and it is undeniable the influence that it has had in Peru. However, it is also unquestionable that during the last decade, the country has suffered from critic mismanagement, called «centralism». In this context, the author gives an overview of the state of the natural gas industry in Peru. Finally, he makes reference to researches aimed at gaining access to natural gas outside the capital.